STUDENT'S PERCEIVED CONFIDENCE IN WRITING PUBLISHABLE ARTICLES - Purwanti, Mariana Sri; Kastuhandani, Fidelis Chosa (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
There has been an increasing demand for undergraduate students to do their scholarly research and publish the finding in the form of articles in their final year of study. The importance of writing publishable articles is a repeated and step-by-step process to maintain self-confidence in writing articles. In other words, many students struggle to publish their articles because the rate of successful articles can be affected by the common mistake made. Therefore, this qualitative study aimed to find how undergraduate students perceived confidence in writing publishable articles since they may still have difficulties in writing articles. The researcher used thematic data analysis to summarize data points. This study applied criterion-based sampling as a technique to determine the sample. The total number of participants was 8 students. This study focused on English Language Education Study Program (ELESP) students in semester 8 at Sanata Dharma University who once joined a conference and published their articles. Data were collected from interviews, Focus Group Discussions (FGD), and document analysis. The findings showed that most ELESP students faced some challenges in writing articles. The challenges experienced frequently by students were the use of grammar and vocabulary. Nonetheless, the results showed that ELESP students utilized some online tools and benefited from feedback from other parties to increase their confidence in writing articles.